Corporate Governance Mechanisms and Financial Performance: The Moderating Role of Firm Size in Manufacturing Firms Listed on the Indonesia Stock Exchange - Septia Aldina Putri; Astri Ayu Purwati; Muhammad Rizki (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study investigates the relationship between corporate governance mechanisms, firm size, and financial performance of manufacturing firms listed on the Indonesia Stock Exchange. Drawing upon agency theory and resource-based perspectives, this research examines how board size, the proportion of independent commissioners, and audit committee size influence financial performance, while also considering firm size as a key organizational characteristic. This study employs a quantitative explanatory design using secondary data obtained from annual reports of manufacturing companies over the 2019–2023 period. Panel data regression analysis is applied to test the proposed hypotheses. The findings indicate that corporate governance mechanisms significantly affect financial performance. Specifically, the proportion of independent commissioners and audit committee size show a positive and significant relationship with return on assets (ROA), suggesting that stronger monitoring mechanisms enhance financial outcomes. Firm size also demonstrates a significant positive effect on financial performance, implying that larger firms benefit from economies of scale and better access to resources. These results confirm the governance–performance nexus in an emerging market context. This study contributes to the corporate governance literature by providing recent empirical evidence from Indonesia and highlighting the importance of governance structure and firm characteristics in improving financial performance. The findings offer practical implications for regulators, investors, and corporate managers in strengthening governance practices to achieve sustainable financial performance.